Pendekatan Indeks Vegetasi Untuk Mengevaluasi Kenyamanan Termal Menggunakan Data Satelit Landsat-Tm Di Kota Ambon - Juglans H Pietersz; John Matinahoru; Ronny Loppies (Faculty of Agriculture, Pattimura University, 2015)
The objectives of the research were to obtain correlation model between NDVI (Normalized Density Value Index) and Freshness Index, to examine the capability of Landsat-TM satellite to show opened green space in controlling the effect of heat island, to know the level of freshness in Ambon town, and to produce layout of opened green space of Ambon town in relation with the need of freshness of the communities. The result of the research showed that Landsat-TM satellite can be used to detect the green space area of the Ambon town. Based on the classification of NDVI through Landsat-TM satellite, the Ambon town has 899,9 hectares (3 %) of land without vegetation or scarcely vegetation, 1488,71 hectares (4 %) were low density of vegetation, 1495,34 hectares (4 %) were in middle density, and 32060, 58 hectares were in high density. NDVI had a positive correlation to the temperature and relative humidity which means that increasing of vegetation density decreased the temperature and increased the relative humidity of a certain area. Effect of the heat island to the Ambon town are identified 1267,93 hectares, and generally found in the central of town (District of Sirimau) and the new development area which followed the main road area.